Pengaruh Inang Alternatif terhadap Kepadatan Populasi Nematoda Entomopatogen Steinernema spp. - Purnomo, Hari; Vintyas, Rohmawati Mufita (Universitas Sebelas Maret, 2022)
The advantages of EPN (Entomopathogenic Nematodes) as a biological agens are it is safe for the environment, effective in controlling pests found above ground and underground in a relatively fast time, and can be easily propagated. EPN propagation is generally carried out in vivo, namely propagation using insect larva. The larvae that are often used are Tenebrio molitor, Galleria melonella, but these larvae are difficult to provide in large quantities. Therefore, it is necessary to find insect media that are cheap, easy to obtain and easy to use by farmers, one of which is Hermetia illucens larva and Alphitobius diaperinus larva. The study aimed to determine alternative host types for the production of entomopathogenic nematodes. The experiment used a completely randomized design (CRD) consisting of two factors. There were two tests carried out, namely a single test to determine the nematodes produced from each alternative host and a mortality test of T. molitor larvae. The concentration used for the single test was 200 JI/0.5 ml and was repeated 30 times. The mortality test for T. molitor larvae consisted of the first factor being the dose of EPN, namely 200 JI/ml, 400 JI/ml, 600 JI/ml, 800 JI/ml, and 1000 JI/ml. The second factor is the origin of NEP isolates from various agro-landscapes with 11 treatments repeated 3 times. Based on these several treatments, observations were made on the Lethal Concentration (LC) and the amount of JI production from each test insect. The highest EPN production is using T.molitor from Bangsal soybean isolate up to 4993,8 Juvenil, this production yield was higher than using larvae of A. diaperinus and H. illucens. the highest percentage of mortality in Bangsal soybean isolate with a concentration of 200 ji/ml up to 53.3%.